Phytoremediation of Leachate Processing at Griya Mulya Landfill, Sidoarjo, Indonesia with Continuous System - Hamidah, Laily Noer; Widiyanti, Atik (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Waste is a global problem that is very hard to solve. Waste generation produces leachate that is harmful to the environment. Leachate can seep into the soil causing direct soil and groundwater pollution. Phytoremediation is an effort to use certain plants and their parts to reduce chemical substances in waste and environmental pollution problems. In this study, the plants used were Typha latifolia by varying the number of plants: without plants, four, and five plants. The leachate used comes from the Griyo Mulya landfill, Sidoarjo. The reactor used was 30´30´50 cm and the discharge used was 15 L/day. The reactor used is a continuous system. The parameters analyzed included TDS and NH3. The results showed that the most significant decrease in TDS and NH3 levels was obtained from the reactor of four and five plants with 700 mg/L of TDS and 10.65 mg/L of NH3.